Epidemiology of Pemphigus - Khalaf Kridin; Enno Schmidt (Elsevier, 2021)
Pemphigus is an epidemiologically heterogeneous group of autoimmune bullous diseases comprising pemphigus vulgaris (PV), pemphigus foliaceus, paraneoplastic pemphigus, IgA pemphigus, and pemphigus herpetiformis. Recently, our knowledge about the frequency of pemphigus, which is highly variable between different populations, has considerably expanded, and the first non-HLA genes associated with PV have been identified. In addition, a variety of comorbidities, including other autoimmune diseases, hematological malignancies, and psoriasis, have been described in this variant. Here, initial data about the impact of COVID-19 on this fragile patient population are discussed and perspectives for future epidemiological studies are outlined.